Peningkatan Hasil Belajar Menulis Kalimat Transitif dan Intransitif Melalui Model Problem Based Learning Siswa Kelas IV A - Nuril Dwi Ramadhani; Bekti Wirawati; Nunuk Suliyastuti (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The purpose of this classroom action research is to use the problem-based learning paradigm to improve the skills of twenty-four fourth-grade students at SDN Pakis 1 Surabaya in producing transitive and intransitive sentences. Methods such as observation, testing, and documentation were used to collect data. Two phases formed this investigation. Students of class IV A improved their learning outcomes for the formation of transitive and intransitive sentences according to the classroom action research. In cycle I, the average score was 72, or 45%, or 11 students. In cycle II, it jumped to 80, or 83%, or 20 students. This study found that in the 2024-2025 academic year, students in class IV A at SDN Pakis 1 Surabaya were able to improve their capacity to create transitive and intransitive sentences by using the problem-based learning paradigm. Problem-Based Learning is known as a learning method that involves identifying a problem and then assigning students to solve it, thus making students more active and able to understand the material during the learning process. Transitive and Intransitive Sentences, Problem-Based Learning (PBL), Classroom Action Research, and Improving Student Learning Outcomes.